Characterization of acute intoxications in Sancti Spíritus pediatric age, 2014-2018 - Yarelyn Prieto Amude; Karen Remedios Rodríguez; Yanicel Sorí León; Yaumara María León Águila; Raylen Escobar Román (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2022)
Background: acute poisoning in children is a serious medical emergency and is considered a growing public health problem worldwide. Objective: to characterize acute intoxications in patients admitted to a pediatric hospital in Sancti Spíritus province from 2014 to 2018. Methods: a descriptive cross-sectional study was carried out from 2014 to 2018. The information was obtained through the review of all the medical records of the admitted patients. The variables age, sex, type of circumstantial poisoning, whether intentional or not, place of occurrence; routes of exposure, hospital stay and responsible agent were analyzed. Absolute and relative frequencies were calculated. Results: accidental poisonings prevailed over voluntary poisonings, both with a tendency to increase. Girls presented the highest percentage, due to intentional causes from 11 years old; boys prevailed in the range of 1 to 5 years due to accidental causes. Medications (66.7%) were the causal agents most involved in both types of poisoning, the digestive tract was the most frequently observed, representing 95.6%. 80.6% of the cases occurred at home and presented a short hospital stay, with three days or less in most of them. Conclusions: exogenous intoxications in children are a cause of morbidity in the Sancti Spíritus province, so it is vitally important to follow up on the results obtained in this research, such as the rate of intoxication by psychotropic drugs.